Improving neurocognitive functioning in schizophrenia by addition of cognitive remediation therapy to a standard treatment of metacognitive training. Issue 2 (6th November 2018) - Caponnetto, Pasquale; Maglia, Marilena; Auditore, Roberta; Bocchieri, Marta; Caruso, Antonio; DiPiazza, Jennifer; Polosa, Riccardo
Abstract : Cognitive dysfunctions are a common clinical feature of schizophrenia and represent important indicators of outcome among patients who are affected. Therefore, a randomized, controlled, monocentric, single-blind trial was carried out to compare two different rehabilitation strategies adopted for the restoration and recovery of cognitive functioning of residential patients with schizophrenia. A sample of 110 residential patients were selected and, during the experimental period, a group of 55 patients was treated with sets of domain-specific exercises (SRT+CRT), whereas an equal control group was treated with sets of non-domain-specific exercises (SRT+PBO) belonging to the Cogpack® software. The effects on the scores (between T0 and T1) of the variables treatment and time and of the interaction time X treatment were analyzed: for the total BACS, the main effect of the between-factors variable treatment is statistically significant (F=201.562 P=0.000), as well as the effect of the within-factors variable " time " (F=496.68 P=0.000).The interaction of these two factors is also statistically significant (F=299.594 P=0.000). The addition of cognitive remediation therapy (CRT) to a standard treatment of metacognitive training (MCT) resulted in a significant improvement in global neurocognitive functioning and has reported positive effects with regard to the strengthening of verbal and working memory, selective and sustained attention at T1. A relevant result is the statistically significance of " time X treatment " for all the tests administered: we can assume that the domain-specific cognitive training amplifies the effects of SRT, as the primary and secondary goals of the present study were achieved.